AB0068 Alarmins s100a8 and s100a9 modulate the inflammatory microenvironment in early tendinopathy. (12th June 2018) - Crowe, L.A.N.; Akbar, M.; Patommel, K.; Kitson, S.M.; Garcia Melchor, E.; Gilchrist, D.S.; Murrell, G.A.; McInnes, I.B.; Millar, N.L.
Abstract : Background: Alarmins- also referred to as damage associated molecular patterns (DAMPS)- are endogenous molecules mobilised in response to tissue damage known to activate the innate immune system in the early stages of disease. The molecular mechanisms that regulate inflammatory and remodelling pathways in tendinopathy are largely unknown therefore identifying early immune effectors is essential to understanding the pathology. S100A8 and S100A9 are constitutively expressed by cells of myeloid origin; under pathological conditions they are induced in other cell types in response to environmental triggers and cellular damage. Objectives: Based on previous investigations we sought evidence of S100A8/A9 expression in human tendinopathy and thereafter, to explore mechanisms whereby S100 proteins may regulate release of inflammatory mediators and matrix synthesis in human tenocytes. Methods: Torn supraspinatus tendon (established pathology) and intact subscapularis tendon (early pathology) biopsies were collected from patients undergoing arthroscopic shoulder surgery. Control samples of healthy hamstring tendon were collected from patients undergoing hamstring tendon ACL reconstruction. S100A8/A9 expression was analysed at transcript and protein level using quantitative RT-PCR and immunohistochemistry, respectively. Primary human tenocytes were cultured from hamstring tendon tissue. The in vitro effect of recombinant human S100A8/A9 on human tenocytes was measured using quantitative RT-PCR and release of inflammatory mediators was measured at protein level by ELISA. Results: Immunohistochemical staining of tendinopathic tissues indicated the presence of S100A8 and S100A9 in tendinopathy with early diseased tissue displaying a distinct increase in S100A8 and S100A9 expression compared with control and established pathology. These findings were mirrored by data obtained at transcript level from both early and late pathology. Treating tenocytes with exogenous S100A8/9 significantly increased release of IL-6 and CCL2; however, no alterations in genes associated with matrix remodelling were observed at a transcript level. Conclusions: The presence of S100A8 and S100A9 in early tendinopathic lesions suggests expression is upregulated in response to cellular damage. We have confirmed the presence of S100A8, S100A9, CCL2 and IL-6 in tendinopathy and propose that S100A8 and S100A9 participate in early pathology by modulating the stromal microenvironment and influencing the inflammatory profile of tenocytes. S100A8 and S100A9 may participate in a positive feedback mechanism involving enhanced leukocyte recruitment and release of pro-inflammatory cytokines from tenocytes that perpetuates the inflammatory response within the tendon in the early stages of disease. This, in turn, may contribute aberrant matrix remodelling and associated morphological deficiencies within the tendon. We propose S100A8 and S100A9 are active alarmins in early tendinopathy that indirectly influence matrix remodelling by perpetuating the stromal inflammatory environment. Selective targeting of DAMP signalling may offer novel therapeutic approaches in the management of human tendon disorders. Reference: [1] Millar NL, et al. MicroRNA29a regulates IL-33-mediated tissue remodelling in tendon disease. Nat Commun2015;6:6774. Disclosure of Interest: None declared